A new black fly species from Brazil, closely related to Simulium guianense Wise (Diptera, Simuliidae), revealed by morphology and DNA barcoding - Hamada, Neusa; Pepinelli, Mateus; Mattos-Glória, Aline; Luz, Sérgio Luíz Bessa (Zootaxa, 2010)
The male, female, pupa and larva of Simulium litobranchium n. sp. are described and illustrated. This new species has 12 gill filaments, as do S. duodenicornium Pepinelli, Hamada & Trivinho-Strixino, S. guianense Wise, S. hirtipupa Lutz, S. perplexum Shelley, Maia-Herzog, Lunas Dias & Couch and S. scutistriatum Lutz, but it can be distinguished from these other species by a combination of characters observed at the pupal and adult stages. DNA barcoding showed that Simulium litobranchium n. sp. exhibits more than 4% nucleotide divergence in cytochrome oxidase I from three other closely related species in the Neotropical subgenus S. (Thyrsopelma). The new species was collected in the Brazilian states of Goiás and Minas Gerais and inhabits rivers 30-40 m in width in the Paraná River hydrographic basin. Females were not observed engaging in anthropophilic behavior. Copyright © 2010 Magnolia Press.
Keywords: Diptera; Hexapoda; Simuliidae; Simulium Guianense; Simulium Hirtipupa; Simulium Nigricoxum; Simulium Scutistriatum